The effect of melasma on self-esteem: A pilot study - J. Jiang; O. Akinseye; A. Tovar-Garza, MD; A.G. Pandya, MD (Wolters Kluwer, 2018)
Melasma is a common disorder of hyperpigmentation characterized by tan or brown macules and patches affecting sun-exposed areas, particularly the face. Melasma has been shown to have a significant impact on the quality of life and self-esteem of those affected. We interviewed six patients who were diagnosed with moderate-to-severe melasma with regard to the effect of their disorder on their self-esteem. All patients reported a significant negative effect on their quality of life and self-esteem. With successful therapy using a triple combination of cream and oral tranexamic acid to treat their melasma, all reported a marked improvement in self-esteem. Physicians who treat patients with melasma should be aware of its profound psychosocial effects and the improvement that successful melasma treatment can have on self-esteem. Keywords: melasma, self-esteem, quality of life, qualitative, pigmentation